DESAIN MASKOT : DINAS KEARSIPAN DAN PERPUSTAKAAN PROVINSI SUMATERA BARAT - Juwita Wirta Sri Depi; Hanafi Malik; Yuni Purnama Sari (Asosiasi Dosen Muda Indonesia, 2024)
The mascot is a creative work created for the West Sumatra Province Archives and Library Service. The mascot with its appeal is expected to be an alternative to increase interest in reading. The mascot design for the West Sumatra Province Archives and Library Service depicts an anatomy book, a deta hat and shoes. Books as bodies Mascots can be interpreted as knowledge. The deta hat on the head is interpreted as a symbol of thought and is also part of the Minangkabau culture. Shoes can be interpreted as meaning that reading is a fun adventure, namely an adventure from one book to another. The method used in creating the Mascot was through observational research methodology, data collection techniques directly within the West Sumatra Archives and Library Service. Documentation, to obtain data from relevant books, journals and images.